IMPACT OF BRACHIARIA, ARBUSCULAR MYCORRHIZA, AND POTASSIUM ENRICHED RICE STRAW COMPOST ON ALUMINIUM, POTASSIUM AND STABILITY OF ACID SOIL AGGREGATES - Hafifa, Bariot; Sabiham, Supiandi; Anas, Iswandi; Sutandi, Atang Sutandi; Suyamto, Suyamto (Indonesian Agency for Agricultural Research and Development - MOA, 2012)
Acid soil is commonly grown with cassava, which in general, tolerate low soilÂ fertility and aluminum (Al) toxicity. However, without any improvement efforts such soil will become worse. Intercropping cassava with Brachiaria decumbens (BD) which adapts to acid soil and tolerates low fertility soils as well as application of arbuscular mycorrhiza (AM) and organic matters are among the important efforts to rehabilitate this soil. The experiment was conducted toÂ examine the impact of BD, AM, and potassium (K) enriched rice straw compost on exchangeable Al, available K, and stability of soil aggregates. Experiment was arranged in a completely randomized design with three factors and three replications. The first factor was BD as cassava intercropping, the second factor was AM, and the third factor was 2 t ha-1 rice straw compost enriched with 0 kg, 50 kg, 100 kg, and 200 kg KCl ha-1. Brick pots (1 m length x 1 m width x 0.45 m depth) filled with Kanhapludult soil was used for growing cassava in which row of BD was planted at 60 cm from cassava stem. K-enriched rice straw compost and AM (10 g per stem) were applied around cassava stem at 2 and 12 days after planting, respectively. BD was cut every 30 days and the cutting was returned to the soil. Soil exchangeable Al was analyzed at 0, 3, 6 and 9 months after planting (MAP), while Al and K contents as well as aggregate stability were measured at 6 MAP. The results showed that planting BD decreased 33% exchangeable Al, which means that the root exudates of this grass was effective in detoxifying Al3+. Treatment of BD and/or in combination with AM was effective in preserving K added to the soil, increasing total polysaccharides, and improving soil aggregate stability. This indicated that planting BD and applying AM and Kenriched rice straw compost improved acid soil fertility, and therefore can be recommended in cassava cultivation.